Investigations of the effects of design parameters on the performance of Rotman type multiple beam forming network - Sharma, PC; Gupta, RD; Singhal, PK (2001)
Modified approach to design Rotman type lens has been proposed. Lenses designed using the proposed approach have been analyzed using the contour integral approach. Effects of design parameters on the performance of the lens have been investigated. Results of investigations on wide band characteristics of the lens are also presented.